Groundwater quality and health risk assessment in the area of LUSI mud volcano in Sidoarjo, East Java, Indonesia: toward clean water sustainability; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 336, № 8 - Adiyaksa I. P. Ilham Putra (2025, 2025)
Relevance. The distribution of clean water that meets acceptable standards is highly needed for public health. However, in many regions of the world, including the eastern part of Java Island (Indonesia), in the East Java province, Sidoarjo, where the world’s largest mud volcano has been active since 2006, this is a significant challenge. This area has a high population density that makes a constant demand for quality drinking water. The ongoing LUSI mud volcano has greatly complicated the issue of the domestic and drinking water supply. As a result, Sidoarjo faces serious challenges, especially given that the only water treatment company – PDAM Delta Tirta Sidoarjo – can serve only 37% of the population. At the same time, the rest of the population must find reliable access to clean water independently. Aim. To analyze the physicochemical characteristics of groundwater around the LUSI mud volcano in Sidoarjo, East Java, Indonesia, and assess the associated health risks from chemical exposure. Methods. Groundwater samples were analyzed for various chemical compounds, and a pollution index was calculated to classify water quality. Additionally, the method recommended by the US Environmental Protection Agency was used to assess the health risks of chemical exposure, including evaluating potential cancer risks. Results and conclusion. An analysis of the groundwater conditions in the area surrounding the world's largest mud volcano, LUSI (Indonesia), was conducted using data obtained by the authors in 2024 and earlier. The authors calculated groundwater saturation concerning various minerals, water quality indices, and health risk assessments associated with water usage. The study revealed that the chemical composition of the examined groundwater is characterized as calcium chloride type, with the overall quality being classified as heavily polluted, particularly due to elevated levels of chlorides and manganese. Based on the Hazard Quotient and Hazard Index, it was determined that the high concentrations of manganese pose a non-carcinogenic health risk, especially for children. Additionally, the Cancer Risk Index analysis showed that, at present, the mercury content in the studied groundwater does not pose a significant health risk. However, ongoing monitoring and remediation of water sources in the LUSI area are highly required to improve groundwater quality as a source of clean water